Association of Serum D-dimer Level with Acute Exacerbation of Chronic Obstructive Pulmonary Disease (AECOPD) - Rashid, Md Mamun or; Khan, Mohammed Shahedur Rahman; Biswas, Bipul Kanti; Yasmin, Sultana; Paul, Chitta Ranjan; Ireen, Romana Afaz; Rashid, H M Aminur; Kabir, Humayoun; Uddin, Muhammad Nasir; Uddin, Muhammad Nasir; et al. (Chest & Heart Journal, 2023)
Background: Chronic obstructive pulmonary disease (COPD) is a major global health problem and is often associated with systemic inflammation. D-dimer level, an end product of degradation of cross-linked fibrin by plasmin, have been shown in some studies to be increased in patients with COPD exacerbation. But still, there is a debate regarding the diagnostic efficiency of D-dimers tests in COPD exacerbation patients. Therefore, this study is aimed to find the association of D-dimer with acute exacerbation of COPD. Methods: This was a cross-sectional study conducted at the National Institute of Diseases of the Chest and Hospital (NIDCH) from March 2020 to February 2021. A total of 90 patients with a confirmed diagnosis of COPD were included after screening in according to the inclusion and exclusion criteria. Following informed written consent, physical examination, relevant investigations were done for all patients. In all cases, ethical issues and health issues were maintained properly and collected data were analysed by SPSS 16. Results: Among 90 COPD patients, mean age of the study population was 56.24±11.24 (SD) years with a majority in age group 51-60 years (50%). Male-female distribution was 97%-male vs 3%-female. Overall frequency of higher D-dimer level was 57.8%. Higher serum D-dimer level was observed in AECOPD patients (p<0.05). Increased serum D-Dimer level was also significantly associated with increased PaCO2 and decreased PaO2. In multivariate analysis, PaCO2 (>45 mmHg) and serum D-Dimer (>0.5 pg /ml) were found to be independent predictors for severe exacerbation of chronic obstructive pulmonary disease. Conclusion:There is association between serum D-dimer level with acute exacerbation of COPD patients. Chest Heart J. 2021; 45(2) : 78-85